Effects and safety of a CBD-rich Cannabis sativa oil in knee osteoarthritis: a double-blind, randomized, placebo-controlled trial – CANOA – cannabis for osteoarthritis - Mojoli, Andrés; Haider, Osvaldo; Fakih, Yasmin; Luz Gonçalves, Maria Victoria; Zepeda Rojas, Bruno; Xaia, Giovanna; Krefta, Emanuelly; Bicca, Maíra Assunção; Lopes de Mari, Thiago; Ferreira, Charles Francisco; Cezar-Dos-Santos, Fernando; Toci, Aline Theodoro; et al. (Frontiers in Pharmacology, 2025)
Osteoarthritis is a common inflammatory and degenerative joint disease characterized by associated chronic pain, often ensuing to diminished quality of life. Current pain management options present small benefits and great side effects, driving interest in potential treatments such as cannabis, for its anti-inflammatory and analgesic effects. This trial aimed to assess the efficacy and safety of cannabidiol (CBD) in a full-spectrum cannabis oil in managing osteoarthritis-related pain.MethodsOsteoarthritis patients were randomized into either placebo or cannabis groups and monitored for 60 days. The cannabis group received a CBD daily oral dose of 45 mg. Primary outcome was determined by pain intensity measured utilizing the WOMAC, while secondary outcomes included the Visual Analogue Scale (VAS) Beck Depression Inventory (BDI), Pittsburgh Sleep Quality Index (PSQI) and the MC S12/PC S12 scores (mental and physical components of the quality of life SF-12 scale).ResultsAt the end of intervention (i.e. 60 days or trial end-point), both the placebo and cannabis groups exhibited comparable improvements in pain scores, with no statistically significant differences in pain intensity observed between groups. Likewise, secondary outcomes showed no significant differences between groups. Furthermore, the CBD-rich cannabis oil was well-tolerated, as no patients experienced any serious adverse events or clinically significant changes in serum biomarkers.ConclusionCBD-rich cannabis oil treatment was well tolerated, with no serious adverse effects observed. However, this treatment did not demonstrate superiority over placebo in alleviating pain or improving secondary outcomes in osteoarthritis patients. Further multicentrical and larger trials are warranted to explore the efficacy of alternative dosages and/or formulations containing CBD, THC and other cannabinoids.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06588972 Identifier: [NCT06588972].